Preventing diabetes after pregnancy with gestational diabetes in a Cree community: an inductive thematic analysis. Issue 1 (11th May 2020) - Pace, Romina; Loon, Orenda; Chan, Deborah; Porada, Helene; Godin, Catherine; Linton, Jonathan; Linton, Paul; Torrie, Jill; Dasgupta, Kaberi
Abstract : Introduction: Historical and political factors underpin the disproportional burden of type 2 diabetes mellitus (T2DM) and gestational diabetes mellitus (GDM) in women, a harbinger of future T2DM, in Indigenous populations. There is a need for T2DM prevention strategies driven by the voices of Indigenous women. In this study, we aimed to understand the perspectives of Cree women with prior GDM living in northern Quebec, where over a quarter of pregnancies are complicated by GDM. Research design and methods: A local healthcare worker invited women with GDM in the prior 5 years to participate in semistructured interviews. A Cree-origin research partner and a researcher jointly conducted interviews in-person or by teleconference. Open-ended questions addressed GDM experience, maintaining a healthy lifestyle, and needs/preferences pertinent to designing a T2DM prevention program aimed at women affected by GDM. We adopted an inductive thematic analysis framework to categorize experiences and opinions. Results: Among the 13 mothers interviewed, some success with health behavior changes during pregnancy was reported but there were difficulties postpartum resulting from time constraints, costs of healthy foods, discomfort at the gym related to not being perceived as athletic, and safety concerns. They acknowledged the existence of programs addressing T2DM prevention in their community but did not participate. They endorsed preferences for group sessions, with family collaboration and childcare, that addressed healthy cooking and physical activity and incorporated traditional elements. Conclusion: Cree mothers with a history of GDM highlighted several barriers to diabetes prevention. We are working to address these barriers through the creation of a Cree-facilitator-led community-based intervention.